A direct numerical simulation analysis of localised forced ignition in turbulent slot jets of CH4/CO2 blends. Issue 1 (March 2023) - Turquand d'Auzay, Charles; Chakraborty, Nilanjan
The early stages of flame evolution following successful localised forced ignition of different CH 4 /CO 2 blends in a slot jet configuration have been analysed using three-dimensional direct numerical simulations. The simulations have been conducted for three different concentration levels of CO 2 in the fuel blend composed of CH 4 and CO 2 (ranging from 0% to 20% by volume). The effects of CO 2 concentration have been analysed based on five different energy deposition scenarios which include situations where the mean mixture composition at the ignitor varies, but not its location in space, whereas other cases represent the scenarios where the mean mixture composition within the energy deposition region remains constant, but its spatial location changes with CO 2 concentration. The most favourable region for successful flame development following thermal runaway, from the mixture composition standpoint (i.e. the highest flammability factor), has been found to be displaced close to the nozzle with an increase in CO 2 concentration. The flame development following thermal runaway exhibits initial growth of hot gas kernel followed by downstream advection and eventual flame propagation along with radial expansion with a possibility of flame stabilisation irrespective of the level of CO 2 concentration. The triple flame propagation has been found to play a key role in the upstream flame propagation and eventual stabilisation. The orientation of the local flame normal plays a key role in the flame stabilisation. The lift off height has been found to increase with increasing CO 2 concentration which also adversely affect flame stabilisation for high levels of CO 2 concentration.